Relação entre depressão e desequilíbrio postural em idosos que sofreram acidente vascular encefálico - Tanaka, Ana Flávia Dias; Scheicher, Marcos Eduardo [UNESP] (Pontifícia Universidade Católica do Paraná (PUC-PR), 2013)
INTRODUCTION: The incidence of stroke it increases with the aging and each successive decade above 55 years leads to a doubling of stroke incidence. Among the current complications of stroke are the unbalance postural and depression. OBJECTIVES: To evaluate and correlate the postural balance and depression in elderly with and without stroke. MATERIALS AND METHODS: We evaluated 38 subjects (19 with stroke and 19 without). The balance was evaluated by Berg Balance Scale and the depression by Yesavage Depression Scale. RESULTS: Elderly with stroke presented depression when compared with elderly without the disease (p < 0.0001). The risk of falling in elderly with stroke was 102 times higher than in elderly without stroke. There was a correlation between depression and balance (r = -0.55; p = 0.01). CONCLUSION: Elderly patients with sequels of stroke have unbalance and greater depression, when compared with elderly of same age without the disease.

INTRODUÇÃO: A incidência de Acidente Vascular Encefálico (AVE) aumenta com o envelhecimento e duplica a cada década de vida a partir dos 55 anos de idade. Entre as complicações decorrentes de um AVE estão o desequilíbrio postural e a depressão. OBJETIVOS: Avaliar e correlacionar equilíbrio postural e depressão em idosos com e sem AVE. MATERIAIS E MÉTODOS: Foram avaliados 38 sujeitos (19 com AVE e 19 sem AVE). O equilíbrio foi avaliado pela Escala de Equilíbrio de Berg e a depressão pela Escala de Depressão de Yesavage. RESULTADOS: Idosos com AVE apresentaram depressão quando comparados com idosos sem a doença (p < 0,0001). O risco de cair em idosos com AVE foi 102 vezes maior do que em idosos sem AVE. Houve correlação entre depressão e equilíbrio (r = -0,55; p = 0,01). CONCLUSÃO: Pacientes idosos com sequelas de AVE apresentam maior desequilíbrio e maior depressão, quando comparados com idosos de mesma faixa etária sem a doença.
Relationship between depression and postural imbalance in the elderly who have suffered stroke
Keywords: Acidente Cerebral Vascular; Quedas; Depressão; Stroke; Falls; Depression